2020
DOI: 10.1101/2020.12.22.424026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WormPaths:Caenorhabditis elegansmetabolic pathway annotation and visualization

Abstract: In our group, we aim to understand metabolism in the nematode Caenorhabditis elegans and its relationships with gene expression, physiology and the response to therapeutic drugs. On March 15, 2020, a stay-at-home order was put into effect in the state of Massachusetts, USA, to flatten the curve of the spread of the novel SARS-CoV2 virus that causes COVID-19. For biomedical researchers in our state, this meant putting a hold on experiments for nine weeks until May 18, 2020. To keep the lab engaged and productiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…2 A). Zhang and coworkers 23 suggested that the ORF8 protein is able to interfere with the antigen presentation, affecting the process of recognition and elimination of the virus by cytotoxic T cells.
Figure 2 ORF8 protein and its interaction with MHC-I.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A). Zhang and coworkers 23 suggested that the ORF8 protein is able to interfere with the antigen presentation, affecting the process of recognition and elimination of the virus by cytotoxic T cells.
Figure 2 ORF8 protein and its interaction with MHC-I.
…”
Section: Resultsmentioning
confidence: 99%
“…ORF6 displays a critical antagonistic activity, avoiding the antiviral innate immune response, inhibiting interferon β (IFN-β) production and blocking the expression of STAT1-activated genes to SARS-CoV 20 , 49 . ORF8 has been considered one of the most relevant proteins related to viral replication in humans, as it is able to inhibit the expression of IFN- β 20 , 50 . The SARS-CoV-2 N protein acts as an IFN-I antagonist regulating the synthesis and signaling of this route.…”
Section: Resultsmentioning
confidence: 99%
“…The precise anti-viral mechanism of teicoplanin has also not been determined. It has however been suggested that teicoplanin potently block the entry of SARS-CoV-2 through the inhibition of the enzymatic activity of cathepsin L [ 43 ]. Based on this, the authors recommended the use of teicoplanin in both prophylaxis and therapeutic management of patients with SARS-CoV-2 infection [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, given that there are different mutations across the different emerging SARS-CoV-2 variants, vaccines were found to be effective against all these mutations. As such, the Pfizer-BioNtech BNT162b2 vaccine has successfully induced neutralisation against the panel of the aforementioned spike protein mutations across different SARS-CoV-2 variants [ 55 ].…”
Section: Comparative Analysis Of Different Coronavirus and Sars-cov-2mentioning
confidence: 99%
“…Other SARS-CoV-2 variances (B.1.1.7, B.1.351 & P.1) have also shown various spike protein mutations (N501Y, P681H, K417N, E484K and K417T), in which enhances the binding affinity of S protein for ACE-2 receptor at a greater extent [ 51 – 55 ]…”
Section: Comparative Analysis Of Different Coronavirus and Sars-cov-2mentioning
confidence: 99%